Dinamika Pembelajaran PAI di Era Digital : Integrasi Teknologi dalam Model Hannafin-Peck untuk pembelajaran yang lebih dinamis - Nugraha, Mulyawan Safwandy; Awwalina, Linlin Sabiqa; Dedih, Ujang (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study discusses the dynamics of Islamic religious education (PAI) learning in the digital era by integrating technology into the Hanafin-Peck model to create more dynamic learning. This research uses qualitative methods with a phenomenological approach through in-depth interviews with teachers, students, and principals. The results showed that integrating technology into PAI learning increased student motivation and engagement. The Hannafin-Peck model provides a comprehensive framework for designing PAI learning experiences that are more contextual and relevant in the digital age. This model focuses on learning needs analysis, technical development of learning strategies, application of digital tools, and continuous assessment. The research concludes that the application of this model can make PAI learning more dynamic and interactive to meet the needs of digital native students. The study's recommendation is the need for continuous innovation in PAI learning to keep pace with technological developments and student needs.